2021
DOI: 10.1016/j.resuscitation.2021.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proenkephalin A 119–159 and dipeptidyl peptidase 3 on admission after cardiac arrest help predict long-term neurological outcome

Abstract: Background: A large proportion of adult survivors of cardiac arrest have a poor neurological outcome. Guidelines recommend multimodal neuroprognostication no earlier than 72À96 h after cardiac arrest. There is great interest in earlier prognostic markers, including very early markers at admission. The novel blood biomarkers proenkephalin A 119À159 (penKid), bioactive adrenomedullin (bio-ADM) and circulating dipeptidyl peptidase 3 (cDPP3) have not been previously investigated for the early prognosis of cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Notably, we revealed here that lower circulating Dpp3 enzymatic levels are associated with a worse skeletal phenotype; conversely, in sepsis, cardiogenic shock, heart failure, and acute kidney injury the correlation goes in the opposite direction, with higher levels resulting in more severe disease and reduced survival rate [19][20][21][22][23][24][25]. In these conditions, angiotensin 2, the primary effector of the renin-angiotensin system (RAS), is recognized as the key substrate of Dpp3 activity and clinical evidence has been interpreted based on the modulation of the RAS by Dpp3, and the resulting impact on hemodynamics and on the physiology of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 77%
“…Notably, we revealed here that lower circulating Dpp3 enzymatic levels are associated with a worse skeletal phenotype; conversely, in sepsis, cardiogenic shock, heart failure, and acute kidney injury the correlation goes in the opposite direction, with higher levels resulting in more severe disease and reduced survival rate [19][20][21][22][23][24][25]. In these conditions, angiotensin 2, the primary effector of the renin-angiotensin system (RAS), is recognized as the key substrate of Dpp3 activity and clinical evidence has been interpreted based on the modulation of the RAS by Dpp3, and the resulting impact on hemodynamics and on the physiology of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 77%
“…In a study of patients discharged from an ICU ( n = 1,207), higher p-PENK and p-NGAL levels measured at ICU discharge were associated with poor one-year outcomes, including in patients with low serum creatinine levels at ICU discharge [ 17 ]. These two biological indicators are considered to be good predictors of mortality in patients with acute kidney injury in the ICU [ 33 ]. Our study offers new insight into predicting mortality in patients in the ICU with AKI.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Recent studies have shown that high PENK levels can predict a worsened prognosis in patients with heart failure [21]. Current literature primarily recognizes PENK for its predictive capabilities regarding AKI occurrence [26][27][28][29], and CKD development [30], recovery of kidney function [31], mortality in severe illnesses [17,19,27], extended ICU stays and heightened mortality post-cardiac surgery [32], and recovery from neurological dysfunction [33][34][35]. The novelty of our study lies in demonstrating that plasma PENK not only predicts mortality in ICU patients with AKI but also, when combined with NGAL, significantly enhances mortality prediction in this patient group.…”
Section: Discussionmentioning
confidence: 99%